P3_5 Properties of a Kyber Crystal - Knight, Daniel; Whelan, Evan; Sampson, Branden; Wedge, Symran (Physics Special Topics, 2021)
This paper analysis the required properties for a lightsaber’s ”Kyber Crystal”. We conclude that it must have a power output of around 63.6MW to be able to generate a lightsaber temperature of 7680oK. It must also be able to generate an intrinsic magnetic field of 10.8mT.